1998
DOI: 10.1002/(sici)1521-4141(199804)28:04<1280::aid-immu1280>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Specific engagement of the CD94/NKG2-A killer inhibitory receptor by the HLA-E class Ib molecule induces SHP-1 phosphatase recruitment to tyrosine-phosphorylated NKG2-A: evidence for receptor function in heterologous transfectants

Abstract: It has been recently demonstrated that the CD94/NKG2-A killer inhibitory receptor (KIR) specifically recognizes the HLA-E class Ib molecule. Moreover, the apparent CD94-mediated specific recognition of different HLA class Ia allotypes, transfected into the HLA-defective cell line 721.221, indeed depends on their selective ability to concomitantly stabilize the surface expression of endogenous HLA-E molecules, which confer protection against CD94/ NKG2-A + effector cells. In the present study, we show that a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 36 publications
(44 reference statements)
3
61
0
1
Order By: Relevance
“…The cell lines used in this work are the EBV-transformed class I MHCnegative human B cell line 721.221 (23), 721.221 transfectants, RBL (rat basophilic leukemia) cells, and RBL cells transfected with LIR-1 (24).…”
Section: Cells Mabs and Hla-g Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell lines used in this work are the EBV-transformed class I MHCnegative human B cell line 721.221 (23), 721.221 transfectants, RBL (rat basophilic leukemia) cells, and RBL cells transfected with LIR-1 (24).…”
Section: Cells Mabs and Hla-g Mutationsmentioning
confidence: 99%
“…5, E and F). This is probably because virtually all decidual NK cells express one or more inhibitory receptors capable of interacting with the HLA-G molecules, including LIR-1 and KIR2DL4 (16), or with the HLA-E molecule, including CD94/NKG2A (24,37). Among these three receptors, KIR2DL4 was demonstrated to play a predominant role in preventing the NK-mediated lysis of HLA-G by decidual NK cells (16).…”
Section: Lir-1-mediated Inhibition Of Nk Killing Is Decreased When 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their initial characterization, experimental evidence has demonstrated a role for the heterodimeric CD94/NKG2 receptors in the regulation of immune responses in NK cells (11)(12)(13)(14) as well as subsets of T cells (15,16). Interestingly, while some of the NKG2 gene products, such as NKG2A, form inhibitory heterodimers with CD94, others such as NKG2C and E form activating complexes in association with CD94 and a signaling adaptor molecule DAP12 (14,17).…”
mentioning
confidence: 99%
“…12,13 In contrast, inhibitory NKG2 proteins (NKG2-A and -B) carry immunoreceptor tyrosine-based inhibition motifs (ITIMs). 12,14 Despite their distinct signaling capabilities, NKG2-A, -B and -C receptors have been found to recognize the same ligand, the non-classical HLA class I molecule HLA-E. 15,16 We have previously characterized gene structure and genomic organization of human NKG2 members. 10,17,18 We found that NKG2-A, -C, -E and -F are closely linked (as listed) and of the same transcriptional orientation.…”
mentioning
confidence: 99%